Raw pH fall-out as a sign of a mycorrhizal modifier of Sorghum sudanensis - Giorgio, Masoero; Pier, Giorgio Peiretti; Alberto, Cugnetto; Giusto, Giovannetti (Journal of Agronomy Research, 2018)
The management of symbiotic Microbial Biota (MB) in the soil as agents that promote the yield and health of crops, is aimed at inducing modifications of the phenotype of plants, both over and under the ground. It is here shown, in Sorghumsudanensis plants, that: i) a simple response to MB inoculation is the result of the fall out of the raw pH; ii) the simple NIR scans of leaves can be considered to rapidly classify the outcomes; iii) the raw pH can be considered a key-variable of leaf modifications. An experiment was carried out on Sorghumsudanensis. The plants were seeded in pots and grown for 66 d, and then a control non-inoculated group (C) was compared with thirteen Arbuscular Mycorrhizae (AM) Glomus inoculated groups and with two commercial MB products. A total of 374 raw pH measurements conducted on the leaves showed that the 5.18 pH units in the C group were scaled by -1.9% (P<0.0336) in the MB group and by -3.4% in the AM group (P<0.0001), with a relevant diversity between groups. Direct discrimination of these three groups, by means of smart NIR-SCIO, showed a % reclassification of the C, MB and AM groups of 74%, 59% and 96% in the fresh leaves and of 65%, 51% and 94% in the dried ground leaves, respectively. The composition of the dried leaves, based on a set of 14 variables predicted via NIRS models, plus the total foliar dry weight and percentage, showed a typical increase in protein, ash and hemicellulose, and a typical decrease in the cellulose, dry matter, crude fiber and crop maturity index. These variables were related to the foliar pH, as a key-variable, by means of a PLS standard model (R2 0.81) in which a low pH steadily favored the dry mass weight and, to a lesser extent, the hemicellulose and the digestible NDF contents; on the other hand, a high pH increased the dry matter percentage and the cellulose content of the leaves. As expected, the leaves of the inoculated plants showed a more juvenile ontogenic status. The epigean botanical modifications can be considered harmonic expressions of a luxuriant symbiosis, as testified by the homologous NIR categorization. The outlook for a symbiotic agriculture, with mycorrhizal plants, should consider the raw pH as a multifaceted variable.
Keywords: raw pH; arbuscular mycorrhizal fungi; microbial biota; NIR-Tomoscopy; smart NIR-SCIO; NIRS foliar discrimination; leaf composition; symbiotic agriculture.